Perancangan Aplikasi Manajemen Keuangan Berbasis Android Dalam Studi Kasus Lingkungan Sekolah SMK Gema Bangsa - Baitika, Haqun; Panca Andriyanto, Lely (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
Consumptive behavior that often occurs in society can become a major problem in financial management. As technology and information develop, currently there are various kinds of applications for managing and allocating finances that can be a reference for society, both personally and in the school environment, one of which is an application with the Android operating system. Often manual recording is considered difficult because notes can be lost or forgotten to be recorded. Based on the background of this problem, an Android-based Personal Financial Management application was designed which has features such as income and expenditure input, debt and receivable maturity reminders, expense bill upload, data backup and restore, budget to limit expenses, import data into CSV form., and also transaction reports. The results of user testing obtained from the application that is done are 100% strongly agree, meaning that the application is very agreeable to use and really helps manage finances to be more efficient and effective.